Application of grid task scheduling algorithm RR to evolutionary multi-robotics problem - Matsumura, Y.; Matsuda, M.; Oiso, M.; Ohkura, K.; Fujimoto, N. (2008 World Automation Congress, 2008)
Task scheduling algorithms for evolutionary multi-robotics (EMR) problem in grid computing environments are discussed. In this paper, list scheduling with round-robin order replication (RR) is adopted to reduce waiting times due to synchronization in EMR. Our results show that RR can reduce the synchronous waiting time in comparison with Work Queue (WQ) methods.